Clio’s stepchildren: Anne of Cyprus, Louis of Savoy, and the politics of historiography - Kügle, K (SAGE Publications, 2023)
The historiographical image of Anne of Cyprus (1418–1462), Duchess of Savoy, and her husband, Duke Louis of Savoy (1413–1465), is overwhelmingly negative. The couple undoubtedly encountered serious political difficulties during their reign, but the ‘black legend’ circulating about Anne and Louis since the seventeenth century appears far from justified. It originated with the so-called Chronica Latina Sabaudiae, a text completed shortly after 1487 and probably written by Étienne Morel (c. 1440–1499), a high-ranking cleric who was a supporter of the estranged son of Anne and Louis, Philippe of Savoy (1438–1497). Morel's narrative, its historical and literary context, and its reception in early-modern and modern historiography are examined against the background of contemporaneous Sabaudian and European politics. Morel's polemics seem inspired by the Commentarii genre of historiography cultivated by fifteenth-century humanists such as Enea Silvio Piccolomini. Both the genesis and the reception of Morel's text demonstrate the shifting but unshakeable alliance of historiography and dynastic politics, exemplifying historiography's role in the fabric of power.